2022
DOI: 10.3390/land11020155
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Dust Particles in Atmospheric Air in Krakow (Poland) (Atmospheric Background)

Abstract: For several decades air pollution in Krakow has been a serious and an unresolved environmental and social problem. The causes of high concentration of particulate matter, such as PM10 and PM2.5 in Krakow are both natural and anthropogenic. Nevertheless, the sources of dust pollution have not been fully determined yet. The main source of dust in Krakow is local emissions, however, particles from adjacent areas might also contribute significantly to the pollution. Transboundary dust should also be taken into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
3
2
Order By: Relevance
“…Also, a previous study on the exposure of fly ash in children's homes by Zierold et al [ 32 ] describes fly ash particles as being smoothly spherical and characterized by silicon, sulphur, potassium, calcium and iron [ 33 ]. The soot particles indicated in Pietras's [ 14 ] work had elongated and branched shapes that are different from this study's micrograph. This variation in the micrograph of the soot particles depends on the type and source of fuel used, the combustion process, and smog reactions in the atmosphere [ 14 ].…”
Section: Results and Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Also, a previous study on the exposure of fly ash in children's homes by Zierold et al [ 32 ] describes fly ash particles as being smoothly spherical and characterized by silicon, sulphur, potassium, calcium and iron [ 33 ]. The soot particles indicated in Pietras's [ 14 ] work had elongated and branched shapes that are different from this study's micrograph. This variation in the micrograph of the soot particles depends on the type and source of fuel used, the combustion process, and smog reactions in the atmosphere [ 14 ].…”
Section: Results and Discussioncontrasting
confidence: 88%
“…The soot particles indicated in Pietras's [ 14 ] work had elongated and branched shapes that are different from this study's micrograph. This variation in the micrograph of the soot particles depends on the type and source of fuel used, the combustion process, and smog reactions in the atmosphere [ 14 ]. Soot aggregates deposited on alumino silicate particles: The SEM micrograph in location H ( Fig.…”
Section: Results and Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This may be due to the very small dimensions of these particles, along with the phenomenon of fluorescence, which hampers the registration of spectra. The iron oxide particles are typical for emissions from the metallurgical industry, but they could also be associated with emissions from coal power plants [59]. Similarly, spherical particles and aggregates, with chemical composition comparable to all of those from the crust samples analysed in this study, were observed in the soils sampled near the Zn-Pb metallurgical plant in nearby Bukowno.…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, the origin of the soot particles is difficult to determine. Their morphology, sizes, and shapes vary, depending on type of the fuel burned, combustion processes (temperature, cooling rate of the exhaust gases), and chemical reactions in the atmosphere [59]. Raman micro-spectroscopy analyses provided significant data for the characteristics of these particles.…”
Section: Discussionmentioning
confidence: 99%